Slotted Beam-Column Energy Dissipating Connections: Applicability and Seismic Behavior - Xin Zhao; Ai Qi (Advances in Civil Engineering)
Energy dissipating joint can effectively strengthen the connection of prefabricated buildings. In the present study, a new slotted mild steel damper was installed at the beam end of the prefabricated structure to form as the energy-dissipating joint of the beam-column. By using ABAQUS software, a finite element (FE) analysis was conducted for the single-story-and-span of the single-frame structure with a slotted damper as energy-dissipating joint. The result shows that the damper was the first to yield in the structure and performed well in energy dissipation, indicating its reasonable design of structure and connection. The energy dissipation mainly occurred at the flange of the variable cross sections, between which beam-ribbed webs ensured the required bearing capacity and stiffness and provided a reliable connection. The hysteretic curves were obtained by analyzing the mechanical properties of the slotted damper under pure bending and pure shearing. In the OpenSees platform, the Steel02 Material model and the twoNodeLink element were used to fit the hysteretic curves; this method was employed for the parametric simulation of the slotted energy dissipation. The dynamic characteristics and seismic response of the controlled structure with slotted energy dissipating joint were also analyzed and compared with those of the uncontrolled structure in the OpenSees platform. The results show that the period of the controlled structure was prolonged and the top story acceleration decreased, indicating its effect in reducing seismic response. The shear-dependent seismic reduction ratio was about 35%, while the drift-dependent seismic reduction ratio was about 10%. The seismic performance of bottom story was better than that of the top story, and the damper has good energy dissipation performance in the bending direction. Some detailed design criteria are put forward and consequences for design on the basis of the performed simulations are shown.